Ambipolar to unipolar irreversible switching in nanosheet transistors: the role of ferrocene in fullerene/ferrocene nanosheets. Issue 10 (14th February 2022) - Mahdaoui, Dorra; Hirata, Chika; Nagaoka, Kahori; Miyazawa, Kun'ichi; Fujii, Kazuko; Ando, Toshihiro; Abderrabba, Manef; Ito, Osamu; Takagi, Makito; Ishimoto, Takayoshi; Tachikawa, Masanori; Yagyu, Shinjiro; et al.
Abstract : The ambipolar triclinic C60 /Fc nanosheet FETs were converted to n-type face-centered cubic C60 nanosheet FETs due to the loss of ferrocene with void formation upon heating at 150 °C. Abstract : Recently, cocrystals containing organic donors and acceptors have been explored as active elements in organic field-effect transistors (FETs). Herein, we report the ambipolar charge transport properties of C60 /ferrocene (C60 /Fc) single cocrystal nanosheets. Upon heating to 150 °C, the ambipolar triclinic C60 /Fc nanosheet FETs were converted to n-type face-centered cubic C60 nanosheet FETs due to the loss of ferrocene with void formation. This thermally induced transition of the crystal structure is accompanied by an irreversible switching of the semiconducting properties of the device from ambipolar to unipolar. We also elucidated the importance of the Fc for the charge transfer properties of the nanosheets using photoemission yield spectroscopy in air and theoretical calculations.